2014
DOI: 10.1016/j.bbabio.2014.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Probing the ubiquinol-binding site of recombinant Sauromatum guttatum alternative oxidase expressed in E. coli membranes through site-directed mutagenesis

Abstract: In the present paper we have investigated the effect of mutagenesis of a number of highly conserved residues (R159, D163, L177 and L267) which we have recently shown to line the hydrophobic inhibitor/substrate cavity in the alternative oxidases (AOXs). Measurements of respiratory activity in rSgAOX expressed in Escherichia coli FN102 membranes indicate that all mutants result in a decrease in maximum activity of AOX and in some cases (D163 and L177) a decrease in the apparent Km (O2). Of particular importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…To use the NADH:O 2 reaction to investigate ubiquinone reduction by complex I it must be rate limiting. Thus, the NADH (200 μM) and O 2 (200-250 μM) concentrations used are substantially higher than the K M values of 79 ± 8 μM for complex I (measured with the NADH:O 2 reaction) and 10-20 μM for AOX (24). Furthermore, the k cat value for NADH oxidation by the flavin in bovine complex I is >5,000 s −1 (25), more than 10 times faster than the maximum rate of NADH:ubiquinone oxidoreduction, so NADH oxidation does not limit catalysis.…”
Section: Resultsmentioning
confidence: 76%
“…To use the NADH:O 2 reaction to investigate ubiquinone reduction by complex I it must be rate limiting. Thus, the NADH (200 μM) and O 2 (200-250 μM) concentrations used are substantially higher than the K M values of 79 ± 8 μM for complex I (measured with the NADH:O 2 reaction) and 10-20 μM for AOX (24). Furthermore, the k cat value for NADH oxidation by the flavin in bovine complex I is >5,000 s −1 (25), more than 10 times faster than the maximum rate of NADH:ubiquinone oxidoreduction, so NADH oxidation does not limit catalysis.…”
Section: Resultsmentioning
confidence: 76%
“…Mutation of any one of these six residues is extremely detrimental to AOX activity. In addition, research has shown that specific mutations in other critical residues partially or completely inactivate AOX [ 24 , 25 , 26 , 27 , 28 , 29 ]. Overall, these important residues are conserved between TbAOX, wheat AOX, HvAOX, and OsAOX isoforms, underscoring their relevance across species ( Table S2 ), [ 12 ].…”
Section: Probing Aox Function: Is Past Performance An Indicator Ofmentioning
confidence: 99%
“…The conserved T219S substitution seen in the monocots above may have steric implications, due to the lost methyl group, and this may affect the three-dimensional structure of the protein and change functionality in ways that are currently unknown. There is also an R96A substitution in OsAOX1d which, in other species, causes a drastic loss of activity ( Figure 2 , Table S2 ) [ 28 ]. A deterioration of OsAOX1d efficiency is, therefore, a viable hypothesis.…”
Section: Probing Aox Function: Is Past Performance An Indicator Ofmentioning
confidence: 99%
See 2 more Smart Citations